PSYCHOMETRIC EVALUATION OF THE INDONESIAN VERSION OF THE IPPA-R PEER ATTACHMENT SCALE - Khoyrinnisa Ringganis; Dhia Nada Aldilla; Hasbi Rismi; Fredrick Dermawan Purba; Fitri Ariyanti Abidin (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Adolescence is a transitional period characterized by rapid changes in physical, emotional, cognitive, and social aspects, as well as a shift in attachment patterns from parents to peers as a source of emotional support. This study aims to examine the psychometric properties of the Indonesian version of the Inventory of Parent and Peer Attachment–Revised (IPPA-R) peer attachment subscale. The IPPA-R translation process followed the guidelines of the International Test Commission (ITC) and was administered to 256 adolescents aged 12–15 years in West Java using a convenience sampling technique. Psychometric analysis was conducted through construct validity testing with Confirmatory Factor Analysis (CFA) and reliability using Cronbach's Alpha. The CFA analysis results showed that the peer attachment subscale formed a three-factor structure consistent with the initial theoretical model, namely Trust, Communication, and Alienation. The goodness of fit values of the peer attachment subscale showed a fit model (CFI = 0.99, TLI = 0.99, RMSEA = 0.038, SRMR = 0.074). There were 7 items that were discarded based on SLF values below 0.30. With a Cronbach's Alpha reliability of 0.872, it can be concluded that the Indonesian version of the IPPA-R, consisting of 18 items, is valid and reliable for measuring peer attachment in Indonesia.